The Effect Of Good Corporate Governance On The Profitability Of Banking Companies Listed On The Idx - Anggraeni, Rifka Fitriana; Kartini, Kartini (Ridwan Institute, 2024)
The emergence of economic crisis in Indonesia is caused by poor corporate governance or Good Corporate Governance that will cause corruption. This study aims to determine the effect of managerial ownership, institutional ownership, board of commissioners, audit committee and board of directors on company performance. The sample used in this study is banking companies in Indonesia listed on the IDX which are currently 2020 – 2022 obtained from the IDX website or www.idx.co.id. The analytical tool used to test research hypotheses is multiple regression. The results showed that managerial ownership and the board of directors had a positive effect on the company's performance. Independent Commissioners negatively affect the Company's performance. Meanwhile, institutional ownership and audit committees have no effect on the performance of banking companies.